PARP1 expression in soft tissue sarcomas is a poor‐prognosis factor and a new potential therapeutic target. Issue 7 (7th June 2019) - Bertucci, François; Finetti, Pascal; Monneur, Audrey; Perrot, Delphine; Chevreau, Christine; Le Cesne, Axel; Blay, Jean‐Yves; Mir, Olivier; Birnbaum, Daniel
Abstract : Soft tissue sarcomas (STSs) are aggressive tumors with few efficient systemic therapies. Poly(ADP‐ribose) polymerase‐1 (PARP1) inhibitors represent an emerging therapeutic option in tumors with genomic instability. The genomics of STSs is complex in more than half of cases, suggesting a high level of inherent DNA damage and genomic instability. Thus, STSs could be efficiently targeted with PARP inhibitors. Promising preclinical results have been reported, but few data are available regarding PARP1 expression in clinical samples. We examined PARP1 mRNA expression in 1464 clinical samples of STS, including 1432 primary tumors and 32 relapses, and searched for correlations with clinicopathological features, including metastasis‐free survival (MFS). Expression was heterogeneous across the samples, not different between primary and secondary tumors, and was correlated to PARP1 DNA copy number. In the 1432 primary tumors, the 'PARP1‐high' samples were associated with younger patients, more frequent locations at the extremities, superficial trunk and head and neck, more leiomyosarcomas and other STSs and less liposarcomas and myxofibrosarcomas, more grade 3, more high‐risk CINSARC tumors, and more 'chromosomically instable' tumors. They were associated with shorter MFS, independently of other significant prognostic features, including the CINSARC signature. We found a strong involvement of genes overexpressed in the 'PARP1‐high' samples in cell cycle, DNA replication, and DNA repair. PARP1 expression refines the prediction of MFS in STSs, and similar expression exists in secondary and primary tumors, supporting the development of PARP1 inhibitors. Abstract : We examined PARP1 mRNA expression in 1464 clinical samples of soft tissue sarcomas (STSs), including 1432 primary tumors. The 'PARP1‐high' samples were associated with shorter metastasis‐free survival, independently of other prognostic features, and with expression of genes involved in cell cycle, DNA replication, and DNA repair. PARP1 expression refines the prognostication in STSs and supports the development of PARP1 inhibitors.